Development and Testing of Lab in a Box: A Portable and Low-cost Electronics Trainer Kit intended for Computer Engineering Students - Benatiro, Louille Glen A.; Cañete, Luis Gerardo S. (International Journal of Computing Sciences Research, 2023)
Purpose – The COVID-19 pandemic brought about the temporary physical closure of educational institutions globally, ushering in the shift to remote learning setups. This highlighted challenges with courses that require practical, hands-on instruction, such as with Electronics laboratory courses. In response, the researcher has proposed the development and testing of Lab in a Box, aimed to a portable and low-cost Electronics trainer kit powered by a Raspberry Pi Zero single-board computer. The device will enable students to perform hands-on Electronics laboratory activities and experiments in a remote or hybrid learning setup. Device development is ongoing as of writing. The completed device will feature Electronics laboratory equipment functionalities contained in a compact, portable case. A complementary software application to control the device, named LABSoft, is also in development. Initial real-world testing will be conducted with Computer Engineering students taking up introductory Electronics laboratory courses at the University of San Carlos, Philippines. Numerous issues were encountered during development, particularly regarding LABSoft’s initial frame rate performance running on the single-core Raspberry Pi Zero. In this paper, a few optimizations, along with the current development progress, are discussed. Method – The data block size of each data transfer using direct memory access (DMA), which is used to continually sample, copy, and store data for the oscilloscope functionality, was timestamped and profiled to determine the optimal block size. The initial graphical user interface toolkit that was used in LABSoft, which was GTK+, was switched to FLTK. Results – The use of the determined optimal DMA data block size of 2,000 samples per block, along with the switch to a different graphical user interface toolkit, allowed LABSoft to reach its target frame rate of 25 frames per second, a considerable improvement from the initial 2 to 3 frames per second performance. Conclusion – The optimizations performed were successful in that it greatly improved the frame rate performance of LABSoft. The single-core Raspberry Pi Zero still proves to be a capable platform for the requirements of the Lab in a Box device. Recommendations – Further performance evaluations during the development of Lab in a Box are recommended to ensure that the Raspberry Pi Zero is still performant despite the added features and functionalities. In addition, other DMA data block size values can be investigated and tested to compare against the determined optimal size of 2,000 samples per block. Practical Implications  – The successful development of Lab in a Box will provide students with a portable and affordable Electronics test and measuring device, which will allow them to perform hands-on Electronics class experiments or projects outside of a classroom or laboratory setting.